Implementation of Critical Chain Project Management Method on Controlling the Pipeline Project - Sandora, Rina; Tridya, Dini Rosyadah (Tibuana, 2025)
In the implementation of construction projects, the incompatibility between plan and actual schedule that cause an additional time and cost is oftenly occurring. The Pipeline Project started in July 2022 and scheduled for completion in November 2022. However, in actuality the project finished in July 2023. Based on this case, an acceleration method needs to be implemented so that the project can be completed quickly and efficiently. One of the methods applied is Critical Chain Project Management (CCPM). Scheduling is carried out using the actual duration of the project that applied with CCPM. The actual duration of the project is 318 days. Furthermore, by using the CCPM, the duration is become 216 days. So, by using the CCPM, the project is completed 32.08% faster than the actual duration of the project. Based on the results of the analysis, by applying the CCPM method is able to make an optimal duration of the project.